The Concentration of Acrylamide in Different Food Products: A Global Systematic Review, Meta-Analysis, and Meta-Regression. Issue 6 (18th August 2022) - Mousavi Khaneghah, Amin; Fakhri, Yadolah; Nematollahi, Amene; Seilani, Fatemeh; Vasseghian, Yasser
ABSTRACT: The current study was devoted to evaluate the concentration of acrylamide among different food products based on subgroups such as type of product, country, and analytical methods with the aid of a meta-analysis. Additionally, the impacts of the human development index (HDI) and gross domestic product (GDP) on acrylamide concentration were discussed using a meta-regression analysis. In this context, some of the international databases such as Scopus, PubMed, Web of Science, and Embase were screened up to 1 September 2019. The meta-analysis of 47 articles including of 230 studies showed that the order of overall rank correlated with average acrylamide concentration in foodstuffs (based on the proposed categories in the original articles) was Potato-based food (740.33 µg/kg) > Fried foods (328.65 µg/kg) > Breakfast cereals (263.27 µg/kg) > Coffee (234.54 µg/kg) > Chocolate (233.68 µg/kg) > Baby infant foods (156.30 µg/kg) > Bread (133.12 µg/kg) > Biscuit (116.42 µg/kg) > Dessert (109.27 µg/kg) > Cake (75.65 µg/kg) > Cereal-base foods (59.48 µg/kg) > Nuts (20.38 µg/kg). The liquid chromatography (LC) based methods followed by gas chromatography (GC) (with derivatization) coupled with mass spectrometry (MS) are the most popular analytical techniques used in acrylamide quantification. Also, with decreasing in GDP as well as the HDI rankings, a significant increase in the concentration of acrylamide was underlined demonstrating a significant effect of socio-economic parameters on acrylamide concentration. In conclusion, the highest acrylamide concentration is observed in potato-based products which can be correlated with their high acrylamide's precursor's content especially free asparagine. Graphical abstract: uf0001